2018
DOI: 10.1021/acs.jpcb.8b07140
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Disintegration of Human Serum Albumin Fibrils under Physiological Conditions: Biophysical Aspects

Abstract: An anomaly in the protein folding process can lead to aggregation or fibrillation of proteins which has been related to neurodegenerative and peripheral diseases. Therefore, it is important to understand the mechanism of prevention of aggregation/fibrillation and to design suitable inhibitors for this process. Literature information suggests that most of the work on these systems has been done on heat induced fibrils (57–65 °C). As a step ahead, in the present study, efforts have been made to understand the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…40 Mukhija et al recently investigated the effect of SDS on the amyloid fibrillation of human serum albumin (HSA) under physiological conditions and found that the micelle form of SDS could not only inhibit the HSA fibrillation process but also effectively disintegrate HSA fibrils. 27 Ismael et al recently found that SDS can induce amyloid fibrillation of IgG at lower concentrations and inhibit protein aggregation at higher concentrations. 41 In addition, SDS is a well-known surfactant which is able to promote the formation of amyloidbeta oligomer, an intermediate cytotoxic structure during amyloid fibrillation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Mukhija et al recently investigated the effect of SDS on the amyloid fibrillation of human serum albumin (HSA) under physiological conditions and found that the micelle form of SDS could not only inhibit the HSA fibrillation process but also effectively disintegrate HSA fibrils. 27 Ismael et al recently found that SDS can induce amyloid fibrillation of IgG at lower concentrations and inhibit protein aggregation at higher concentrations. 41 In addition, SDS is a well-known surfactant which is able to promote the formation of amyloidbeta oligomer, an intermediate cytotoxic structure during amyloid fibrillation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Understanding the modulation factors of amyloid fibrillation is no doubt fundamentally important in amyloid research. It is not only beneficial to the drug discovery in the treatment and prevention of amyloid-related diseases but also beneficial to the development of amyloid-based novel materials. In this work, we aim to investigate the modulation effect of two common surfactants, sodium dodecyl sulfate (SDS) and Triton X-100 (TX-100), on amyloid fibrillation using hen egg white lysozyme (HEWL) as a model protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once they get confined within a viscous and restricted environment or in highly ordered nano cavity, radiative transitions are significantly enhanced, thereby suppressing the nonradiative ones and eventually leading to an increase in the fluorescence intensity. , Owing to its unique photophysical properties, over the years ThT has been engaged as a biomarker for the identification of misfolded protein aggregates viz. amyloid fibril both in “ in vivo ” and “ in vitro ” systems. Recently, it has been reported that ThT can also be used to recognize G-quadruplex and guanine-rich non quadruplex DNA duplex through a turn-on fluorescence mechanism. , However, several research approaches are being presently pursued to establish better insights into the DNA-binding mechanism of ThT for the development of advanced DNA biosensors. Although there are few reports on the interaction between ThT and dsDNA (calf thymus DNA), there are no comprehensive reports which help us to understand the binding kinetics of ThT with different 20 base pair (bp) long dsDNA having diverse base pair compositions.…”
mentioning
confidence: 99%
“…The protein solutions were subjected to extensive dialysis at 4 °C with a minimum of three changes followed by determining its concentration on a Jasco V-550 double beam spectrophotometer using an extinction coefficient corresponding to A 280 1% = 5.8. 35 The weight measurements were done on a Sartorius BP 211D digital weighing balance with a readability of 0.01 mg.…”
Section: Methodsmentioning
confidence: 99%